Hardware-in-the-loop Test for a Parabolic Trough Collector Plant in the Meat Industry. (June 2016) - Hassine, Ilyes Ben; Pietruschka, Dirk
Abstract: The paper presents the concept, implementation and results of the hardware-in-the-loop test bench (HiL) established for a medium-scale parabolic trough collector system under construction. The 122.4m 2 plant heats the make-up water of a fossil-fired steam boiler in a meat factory in Austria. The test bench consists of a plant model implemented in a Real-Time machine, which is electrically connected to the plant control hardware (PLC) through several I/O terminals. Within the test bench, it is possible to run different test cycles and emulate critical operation scenarios like collector loop overheating. The control strategy of the solar plant can be checked with minimal risk. The test bench also enables to improve the control ability to cope with weather and sensor disturbances. A suitable fault detection strategy is prepared, which minimizes the risk of component damage and enhances the plant availability.